Reusable Nano-Zirconia-Catalyzed Synthesis of Benzimidazoles and Their Antibacterial and Antifungal Activities - Tentu Nageswara Rao; Suliman Yousef AlOmar; Faheem Ahmed; Fadwa Albalawi; Naushad Ahmad; Nalla Krishna Rao; M. V. Basaveswara Rao; Ravi Kumar Cheedarala; G. Rajasekhar Reddy; Tentu Manohra Naidu (Molecules, 2021)
In this article, a zirconia-based nano-catalyst (Nano-ZrO2), with intermolecular C-N bond formation for the synthesis of various benzimidazole-fused heterocycles in a concise method is reported. The robustness of this reaction is demonstrated by the synthesis of a series of benzimidazole drugs in a one-pot method. All synthesized materials were characterized using 1HNMR, 13CNMR, and LC-MS spectroscopy as well as microanalysis data. Furthermore, the synthesis of nano-ZrO2 was processed using a standard hydrothermal technique in pure form. The crystal structure of nano-ZrO2 and phase purity were studied, and the crystallite size was calculated from XRD analysis using the Debye–Scherrer equation. Furthermore, the antimicrobial activity of the synthesized benzimidazole drugs was evaluated in terms of Gram-positive, Gram-negative, and antifungal activity, and the results were satisfactory.